HUBUNGAN KARAKTERISTIK DEMOGRAFI DAN GAYA HIDUP DENGAN PERILAKU PENUKARAN POINT REWARD KARTU KREDIT DI KOTA DENPASAR - Melia, Melia; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen, 2014)
ABSTRACT The purpose of this study was to determine the relationship of demographic characteristics (gender, age, education, and income) and lifestyle with onsite behavior reward point credit cards for credit card users in the city of Denpasar. This study is targeting customers of Bank Mandiri and BCA Soerapatti Branch Branch, with each sample as many as 50 customers. Data were collected by distributing questionnaires then processed using Chi-square analysis techniques. The results of data processing show that among the four demographic variables, only income had a significant relationship with the behavior of credit card reward point redemption. Lifestyle also does not have a significant relationship with the behavior of credit card reward point redemption. Keywords : demographics, lifestyle, credit card reward points